Emissions embodied in global trade have plateaued due to structural changes in China. Issue 9 (28th September 2017) - Pan, Chen; Peters, Glen P.; Andrew, Robbie M.; Korsbakken, Jan Ivar; Li, Shantong; Zhou, Dequn; Zhou, Peng
Abstract : In the 2000s, the rapid growth of CO2 emitted in the production of exports from developing to developed countries, in which China accounted for the dominant share, led to concerns that climate polices had been undermined by international trade. Arguments on "carbon leakage" and "competitiveness"—which led to the refusal of the U.S. to ratify the Kyoto Protocol—put pressure on developing countries, especially China, to limit their emissions with Border Carbon Adjustments used as one threat. After strong growth in the early 2000s, emissions exported from developing to developed countries plateaued and could have even decreased since 2007. These changes were mainly due to China: In 2002–2007, China's exported emissions grew by 827 MtCO2, amounting to almost all the 892 MtCO2 total increase in emissions exported from developing to developed countries, while in 2007–2012, emissions exported from China decreased by 229 MtCO2, contributing to the total decrease of 172 MtCO2 exported from developing to developed countries. We apply Structural Decomposition Analysis to find that, in addition to the diminishing effects of the global financial crisis, the slowdown and eventual plateau was largely explained by several potentially permanent changes in China: Decline in export volume growth, improvements in CO2 intensity, and changes in production structure and the mix of exported products. We argue that growth in China's exported emissions will not return to the high levels during the 2000s, therefore the arguments for climate polices focused on embodied emissions such as Border Carbon Adjustments are now weakened. Plain Language Summary: In the 2000s, CO2 emissions from production in developed countries flattened while emissions from their consumption grew. The rapid growth of exported emissions from developing countries to developed countries, with the largest contribution from China, played a significant role. This led to concerns that climate polices had been undermined by rapid growth in international trade. Since around 2007, growth in these exported emissions has plateaued, predominantly due to changes in China. Our study investigates China's changes, demonstrating that in addition to the effects of global financial crisis, China implemented potentially permanent structural changes. We argue that China's exported emissions are unlikely to return to the growth levels from the 2000s, and therefore trade‐related climate polices will be much less relevant. Key Points: CO2 exported from developing to developed countries has plateaued since 2007 due to a plateau in China's exported CO2 The slowdown in China's exported CO2 was largely explained by improvements in the CO2 intensity and structural change Arguments for Border Carbon Adjustments may become less relevant due to the plateau in Chinese exported emissions